12. SOME ANXIETY FACTORS IN FCAD PATIENTS TREATED WITH MEDLO AND SENSIVE SERUM AT FOB DERMATOLOGY SPECIALIZED CLINIC IN 2022-2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describes some factors related to the anxiety of FCAD patients treated with medlo and intensive serum at the Fob dermatology clinic in 2022-2023. Materials and method: A cross-sectional descriptive study was conducted on 85 patients diagnosed with facial corticosteroid addictive dermatitis (FCAD) who came for examination and treatment at the Fob dermatology clinic from July 2022 to May 2023. Results: Patients with paraanxiety disorder have a rate of 10.6%, and those with anxiety have a rate of 34.1%. There was a change in the rate of anxiety disorders after 12 weeks of treatment: the rate of anxiety before treatment was 34.1% and decreased (16.5%). Conclusion: When treating FCAD patients, it is necessary to pay attention to anxiety disorders in patients, especially those who work mentally and live in cities.
Keywords: FCAD, anxiety, dipotassium glycyrrhizinate, treatment.